2013
DOI: 10.1007/s10519-012-9575-5
|View full text |Cite
|
Sign up to set email alerts
|

Xq27 FRAXA Locus is a Strong Candidate for Dyslexia: Evidence from a Genome-Wide Scan in French Families

Abstract: Dyslexia is a frequent neurodevelopmental learning disorder. To date, nine susceptibility loci have been identified, one of them being DYX9, located in Xq27. We performed the first French SNP linkage study followed by candidate gene investigation in dyslexia by studying 12 multiplex families (58 subjects) with at least two children affected, according to categorical restrictive criteria for phenotype definition. Significant results emerged on Xq27.3 within DYX9. The maximum multipoint LOD score reached 3,884 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Xq27.3 markers showed suggestive association with dyslexia in the female sub‐sample of a study in an Afrikaner population (Platko et al ., ) and suggestive linkage to a nonsense word spelling phenotype in a general population sample (Bates et al ., ). Finally, a recent study of French dyslexic families also supported the DYX9 locus, with maximal linkage at Xq27.3 (Huc‐Chabrolle et al ., ). The authors proposed that variants affecting FMR1 , a gene implicated in fragile X syndrome (the most common genetic cause of intellectual disability), might be involved, although sequencing of this gene and six other candidates ( CXORF1 , CXORF51 , SLITRK2 , FMR2 , ASFMR1 , and FMR1NB ) failed to identify any mutation or polymorphisms co‐segregating with dyslexia.…”
Section: Additional Dyslexia Susceptibility Locimentioning
confidence: 97%
“…Xq27.3 markers showed suggestive association with dyslexia in the female sub‐sample of a study in an Afrikaner population (Platko et al ., ) and suggestive linkage to a nonsense word spelling phenotype in a general population sample (Bates et al ., ). Finally, a recent study of French dyslexic families also supported the DYX9 locus, with maximal linkage at Xq27.3 (Huc‐Chabrolle et al ., ). The authors proposed that variants affecting FMR1 , a gene implicated in fragile X syndrome (the most common genetic cause of intellectual disability), might be involved, although sequencing of this gene and six other candidates ( CXORF1 , CXORF51 , SLITRK2 , FMR2 , ASFMR1 , and FMR1NB ) failed to identify any mutation or polymorphisms co‐segregating with dyslexia.…”
Section: Additional Dyslexia Susceptibility Locimentioning
confidence: 97%
“…Variable expression of gene(s) in Xq27.3, where an X-linked pattern of BPS inheritance has been identified (Santos et al, 2008) and where a marker for dyslexia has also been identified (de Kovel et al, 2004; Huc-Chabrolle et al, 2013), appear to contribute to the expression of a dyslexia behavioral profile. Like other genetic markers for dyslexia, however (Raskind et al, 2012), DYX9 linkage to dyslexia has been inconsistent (Fisher et al, 2013).…”
mentioning
confidence: 99%
“…The subsequent analysis of these TAR-isolated fragments excluded the 750-kb genetically unstable region at Xq27 as a candidate locus for prostate malignancy 36 . The polymorphism information accumulated during analysis of this region may be useful for the analysis of other disease-associated loci that were also mapped to Xq27-q28, including the TGCT locus linked to hereditary testicular cancer and the susceptibility loci for dyslexia, autism, and migraine 54, 55. In the future, the accumulated information from individual genomes can help predict the pharmaceutical drug response for each individual and expand the therapeutic window of a treatment.…”
Section: Main Textmentioning
confidence: 99%
“…36 The polymorphism information accumulated during analysis of this region may be useful for the analysis of other disease-associated loci that were also mapped to Xq27-q28, including the TGCT locus linked to hereditary testicular cancer and the susceptibility loci for dyslexia, autism, and migraine. 54,55 In the future, the accumulated information from individual genomes can help predict the pharmaceutical drug response for each individual and expand the therapeutic window of a treatment. In addition, the uniqueness of the technology will help with the design of diagnostics for genomic disorders caused by chromosomal rearrangements.…”
Section: Tar Cloning To Study the Genetic Basis Of Human Diseasementioning
confidence: 99%